The Archive of Development - Balkema, Annette W.,; Slager, Henk, (Social Sciences - Book Archive pre-2000., 1998)
In the current debate on art, thought on time has commanded a prominent position. Do we live in a posthistorical time? Has objective art historical time and belief in a continual progress shifted to a more subjective experience of the ephemeral? Has (art) history fallen away and, if so, what does this mean for the future of art? How does a visual archive relate to artistic memory? This volume investigates positions, arguments and comments regarding the stated theme. Philosophers and theorists explore the subject matter theoretically. Curators articulate the practice of art. The participants are: Hans Belting, Jan Bor, Peter Bürger, Bart Cassiman, Leontine Coelewij, Hubert Damisch, Arthur C. Danto, Bart De Baere, Okwui Enwezor, Kasper König, Sven Lütticken, Manifesta (Barbara VanderLinden), Hans Ulrich Obrist, Donald Preziosi, Survival of the Past Project (Herman Parret, Lex Ter Braak, Camiel Van Winkel), Ernst Van Alphen, Kirk Varnedoe, Gianni Vattimo, and Kees Vuyk.